Rural‐urban differences in informal caregiving and health‐related quality of life. Issue 2 (6th May 2021) - Cohen, Steven A.; Ahmed, Neelam; Brown, Monique J.; Meucci, Marissa R.; Greaney, Mary L.
Abstract: Objectives: Rural‐urban health disparities are pervasive among older adults. Rural US locations have a disproportionately high population of older adults, have reduced access to services, and are therefore more reliant on family and friends for care. However, little is known about rural‐urban disparities among the 40+ million informal caregivers nationwide. There is a critical need to understand how rural‐urban disparities impact caregiving experiences and health‐related quality of life (HRQoL). The objectives of this study were to assess rural‐urban differences in informal caregiving status, caregiving intensity (caregiving hours/week and types of care provided), and caregiver HRQoL. Methods: Data were abstracted from the 2018 Behavioral Risk Factor Surveillance System. The primary measure of rural‐urban status was "metropolitan status." Associations between rural‐urban status and caregiving and rural‐urban differences in caregiving intensity and HRQoL were examined using generalized linear models, controlling for confounding and accounting for complex sampling. Results: Rural respondents were more likely to be caregivers than urban respondents (OR = 1.17, 95% CI: 1.02‐1.34). After adjustment for confounders, rural caregivers were more likely than urban caregivers to provide 20 or more hours of caregiving per week (OR 1.38, 95% CI: 1.07‐1.77), although the findings for health and HRQoL were somewhat mixed. Conclusion: Results indicate that rural older adults offer more care than urban counterparts, which may have implications for caregiver health, well‐being, and quality of life. These results can inform policies designed to improve caregiver health, and facilitate the translation and adaptation of existing policies, programs, and interventions to address rural caregivers' needs.